☆Improving IEEE 802.15.4 channel access performance for IoT and WSN devices. (October 2020) - Gezer, Ali; Okdem, Selcuk
Highlights: ACAMRO increases MAC throughput up to 120% compared to default IEEE 802.15.4 setup ACAMRO needs a memory space which is below 20 Kbytes ACAMRO's execution time is shorter than a unit of IEEE 802.15.4 slot time ACAMRO is applicable for tiny IoT and WSN devices Graphical abstract: Abstract: IEEE 802.15.4 is a well-known protocol for low power, low rate wireless personal area networks that determines the specifications for the physical layer and the media access control sub-layer. However, IEEE 802.15.4 suffers from several limitations that play a role in reducing its performance such as using a default maximum backoff (macMaxCsmaBackoffs) value for channel access. In terms of energy efficiency, complexity, delay, using a default macMaxCsmaBackoffs does not provide optimum performance in every channel condition. For this reason, we built an adaptive channel access model, ACAMRO that maximizes channel utilization via adjusting macMaxCsmaBackoffs according to channel conditions. ACAMRO provides higher throughput which yields up to a 120% performance gain compared to the default IEEE 802.15.4 setup. It provides an implementation requiring low memory space that is less than 20 kBytes. Measured results show that ACAMRO achieves significant throughput increase, and a low complexity solution for Internet of Things devices.